PENGARUH MEDIA SMART PARENTING TERHADAP KEMAMPUAN MEDIASI DIGITAL ORANG TUA SELAMA PANDEMI DI TK AL-AZHAR 54 KOTA PEKANBARU - Elvina Putri Setiawan; Ria Novianti; Daviq Chairilsyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Based on observations of parents at Kindergarten Al-Azhar 54 Pekanbaru, it was found that most parents had limited knowledge regarding the dangers of gadget use. Many parents provided excessive freedom to children in using gadgets, did not control the duration of gadget use, did not limit internet content accessible to children, lacked understanding of the impacts of gadget use, and were not able to properly guide children in using the internet appropriately.The purpose of this study was to determine the effect of Smart Parenting media on parents’ digital mediation skills during the pandemic at Kindergarten Al-Azhar 54 Pekanbaru. This study employed a quantitative experimental research design. The sample consisted of 34 parents who had children aged 5–6 years at Kindergarten Al-Azhar 54 Pekanbaru. Data were collected using a true–false objective test.The results showed that there was a significant effect of the use of Smart Parenting media on parents’ digital mediation skills. This was indicated by a tcount value of 18.848, which was greater than the ttable value of 2.035, with a significance value of 0.000 < 0.05. Therefore, H₀ was rejected and Hₐ was accepted, indicating a significant effect of Smart Parenting media on parents’ digital mediation skills. The magnitude of the effect was 78.14%, meaning that 78.14% of parents’ digital mediation skills were influenced by the use of Smart Parenting media.